(untitled) (Medical Forum Monthly, 2024)
Abstract: Polyhydramnios is a relatively uncommon but distressing complication associated with pregnancy. Objective: To find frequency of congenital anomalies with increasing severity of polyhydramnios. Study Design: Prospective Study. Place and Duration of Study: This study was conducted in Lady Willingdon Hospital, Lahore from July 2009 to June 2011. Materials and Methods: Total 170 diagnosed cases of polyhydramnios from 20-41 weeks of gestation were included in the study. Results: Polyhydramnios was diagnosed in 170 pregnancies. Mild polyhydramnios (AFI 24.0-29.9 cm) was found in 112 (65.88%) pregnancies, moderate (AFI 30.0-34.9 cm) in 38 (22.35%) pregnancies and severe (AFI 35.0 cm or more) in 20 (11.76%) pregnancies. Antenatal detection of anomalies was in 71 (41.76%) fetuses. The prevalence of anomalies was higher in pregnancies with more amniotic fluid. A total of 83 anomalies were detected in 71 fetuses. Pregnancies complicated with severe polyhydramnios had maximum number of fetuses with multiple anomalies. 37 pregnant women out of 170 (21.76%) with polyhydramnios had maternal diabetes. Of these 37 pregnancies 11 (29.72%) had pregestational diabetes, 13 (35.13%) had gestational insulin treated diabetes, 13 (35.13%) had gestational diet controlled diabetes. Anomalous fetuses were present in 5 (13.51%) of diabetic pregnancies with polyhydramnios.There were 7 (4.11%) fetal deaths in pregnancies complicated with polyhydramnios. Conclusions: This study proves that pregnancies with severe polyhydramnios have a greater frequency of fetal anomalies. Diagnosis of second trimester polyhydramnios should initiate a search for possible associated fetal anomalies and causative factors.